2023
DOI: 10.1088/2631-6331/acb12a
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of stereolithographic 3D printed boron nitride nanotube-reinforced ceramic composites with improved thermal and mechanical performance

Abstract: Boron nitride nanotubes (BNNTs) are the perfect candidate for nanofillers in high-temperature multifunctional ceramics due to their high thermal stability, oxidation resistance, good mechanical properties, high thermal conductivity, and radiation shielding. In this paper, 3D printed ceramic nanocomposite with 0.1 wt% of BNNT was prepared by fusing it at high temperatures. Samples were built with three different print directions to study the effect of print layers on mechanical performance along with BNNT addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The experimentally measured flexural strength and fracture toughness improvements in BNNT-silica nanocomposites compare favorably with the literature values. For example, the measured flexural strength improvement for 0.1 wt % BNNT-silica nanocomposites (∼51%) is in good agreement with the value (∼55%) reported by Sweat et al Overall, as shown in Figure a,b, the mechanical property enhancements obtained in the present study substantially exceed those reported in the literature (see Table S1), achieving better or comparable reinforcement at much lower filler concentrations. This finding indicates that the high-purity HTP-BNNTs that are of few walls, small diameters, and up to a few hundred microns in length are superior reinforcing fillers for ceramics.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The experimentally measured flexural strength and fracture toughness improvements in BNNT-silica nanocomposites compare favorably with the literature values. For example, the measured flexural strength improvement for 0.1 wt % BNNT-silica nanocomposites (∼51%) is in good agreement with the value (∼55%) reported by Sweat et al Overall, as shown in Figure a,b, the mechanical property enhancements obtained in the present study substantially exceed those reported in the literature (see Table S1), achieving better or comparable reinforcement at much lower filler concentrations. This finding indicates that the high-purity HTP-BNNTs that are of few walls, small diameters, and up to a few hundred microns in length are superior reinforcing fillers for ceramics.…”
Section: Resultssupporting
confidence: 92%
“…Substantial bulk mechanical property improvements of BNNT-reinforced ceramic nanocomposites have been reported. For example, the introduction of 1 wt % BNNTs in zirconia (ZrO 2 ) and Al 2 O 3 reportedly increases the ceramic’s toughness by 65 and 31%, respectively. , The addition of 5 wt % BNNTs in silica (SiO 2 ) reportedly increased the flexural strength by 131% and the fracture toughness by 109% . A recent study reported increases in bending modulus and strength by 72 and 55%, respectively, from the addition of merely 0.1 wt % BNNTs . While these reported bulk mechanical property improvements are useful to demonstrate the reinforcement potentials of BNNTs for ceramics, the underlying reinforcing mechanism remains elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lago et al [25] studied the dependence of the polycarbonate mechanical performances on boron nitride fakes morphology and observed the difference in Young's modulus of 56 MPa, being the increment, compared to pristine polycarbonate with 0.1 wt% of loading. Tank et al [26] studied the mechanical performance of BNNT-reinforced ceramic composite and observed a significant improvements of 55% in bending strength, 72% in bending modulus and 63% in thermal diffusivity with just 0.1 wt% addition of BNNT.…”
Section: Introductionmentioning
confidence: 99%